2020
DOI: 10.1186/s40246-019-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating diagnostic sequencing techniques for CADASIL diagnosis

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebral small vessel disease caused by mutations in the NOTCH3 gene. Our laboratory has been undertaking genetic diagnostic testing for CADASIL since 1997. Work originally utilised Sanger sequencing methods targeting specific NOTCH3 exons. More recently, next-generation sequencing (NGS)-based technologies such as a targeted gene panel and whole exome sequencing (WES) have been used for improved genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
9
0
2
Order By: Relevance
“…Among the non-AD risk genes, such as Notch Receptor 3 ( NOTCH3 ), Leucine-rich repeat kinase 2 ( LRRK2 ), and microtubule-associated protein tau ( MAPT ), several variants appeared, too. A rare mutation, Leu1518Met, was observed in NOTCH3 , but its role in neurodegenerative diseases remained unclear [ 18 ]. Additionally, a common variant was observed in MAPT (Tyr441His), and three common variants appeared in LRRK2 (Arg50His, Ser1647Thr, and Met2397Thr) ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the non-AD risk genes, such as Notch Receptor 3 ( NOTCH3 ), Leucine-rich repeat kinase 2 ( LRRK2 ), and microtubule-associated protein tau ( MAPT ), several variants appeared, too. A rare mutation, Leu1518Met, was observed in NOTCH3 , but its role in neurodegenerative diseases remained unclear [ 18 ]. Additionally, a common variant was observed in MAPT (Tyr441His), and three common variants appeared in LRRK2 (Arg50His, Ser1647Thr, and Met2397Thr) ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that Notch1 and Hes1 molecules are potential biomarkers for mild and moderate/severe TB, providing a basis for adjunctive diagnosis and monitoring of disease efficacy. Previous research has identified Notch3 as a diagnostic marker for cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) ( 32 , 33 ), while DLL1 has shown utility in diagnosing tuberculous meningitis ( 12 ). Although no other Notch signaling molecules have been identified as biomarkers for other diseases, the regulation of immune cells function and cytokines secretion by Notch signaling molecules can affect the outcome of TB disease.…”
Section: Discussionmentioning
confidence: 99%
“…NGS allows for millions of small fragments of DNA to be sequenced at once, allowing for entire gene sets or even the whole genome to be investigated, rather than targeted exons or regions. 15,62,63 Several research groups have reported increased diagnostic rates for several neurological diseases, through the use of whole exome sequencing (WES) [64][65][66] and targeted gene panels. [67][68][69] WES analysis has shown that not all suspected HM cases have exonic mutations in the known FHM genes, 30,31 or genes that cause overlapping disorders, which suggests that additional genes or other factors as yet unknown are causative of HM, 12 some of which may be revealed through WES or whole genome sequencing and structural analysis.…”
Section: Hemiplegic Migrainementioning
confidence: 99%